2020
DOI: 10.1111/all.14326
|View full text |Cite
|
Sign up to set email alerts
|

Association of rhinovirus species with nasopharyngeal metabolome in bronchiolitis infants: A multicenter study

Abstract: Ungar B , et al. Dupilumab progressively improves systemic and cutaneous abnormalities in patients with atopic dermatitis .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…In prior analyses without RV species–level resolution, nasopharyngeal 11 and circulating 12 metabolomic profiles differed between RSV and RV infection. Additionally, our group previously reported between‐virus differences in the nasopharyngeal metabolome 23 . For example, in the RSV vs RV‐A comparison, the discriminatory nasopharyngeal metabolites consisted mainly of nucleic and amino acids (such as guanine and cysteine‐glutathione disulfide).…”
Section: Discussionmentioning
confidence: 97%
“…In prior analyses without RV species–level resolution, nasopharyngeal 11 and circulating 12 metabolomic profiles differed between RSV and RV infection. Additionally, our group previously reported between‐virus differences in the nasopharyngeal metabolome 23 . For example, in the RSV vs RV‐A comparison, the discriminatory nasopharyngeal metabolites consisted mainly of nucleic and amino acids (such as guanine and cysteine‐glutathione disulfide).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, research has also suggested the role of metabolome—which represents the downstream functional products of the microbiome, child’s genetic make-up, and immune response—in the pathogenesis of bronchiolitis and asthma 2 . For example, a recent study of airway metabolome has shown differences in pro- and anti-inflammatory mediators (e.g., spermidine) in infants with bronchiolitis 12 . These studies—while limited to single-level data (e.g., clinical, virus, microbiome, cytokines/chemokines, metabolome)—have discovered potential mechanisms that underlie the bronchiolitis–asthma link.…”
Section: Discussionmentioning
confidence: 99%
“…While bronchiolitis has been considered a single disease with similar mechanisms 2 , emerging evidence suggests heterogeneity in clinical presentations 4 and chronic morbidities (e.g., subsequent risk of recurrent wheeze and asthma) 5 , 6 . Growing evidence also suggests distinct upper airway microbiome 7 , 8 , transcriptome 9 , cytokine 10 , 11 , and metabolome 12 profiles among infants with bronchiolitis. However, these findings have been solely derived from single-level (e.g., clinical or microbiome) data.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators collected nasopharyngeal airway samples within 24 hours of hospitalization using a standardized protocol ( 9 ). These samples underwent A) real-time PCR to test for respiratory viruses ( 2 ), B) ultra-performance liquid chromatography–tandem mass spectrometry to profile the metabolome ( 10 ), and C) 16S rRNA gene sequencing to profile the microbiota ( 11 ).…”
Section: Methodsmentioning
confidence: 99%